Hydrological variability in southern Siberia and the role of permafrost degradation - Han, Li; Menzel, Lucas (Journal of hydrology, 2021)
Changes in the cryosphere caused by global warming are expected to alter the hydrological cycle, with consequences to freshwater availability for humans and ecosystems. Here, we combine data assimilation, cross-correlation analysis, simulation techniques, and the conceptual steady-state Budyko framework to examine the driving mechanisms of historical hydrological changes at annual, seasonal, and monthly scales. We focus on two southern Siberian basins with different landscape properties: the semi-arid Selenga, characterized by discontinuous, sporadic, and isolated permafrost; and the boreal Aldan, which is underlain by continuous permafrost. Our results indicate that the two basins show divergent trends in river runoff over the period 1954-2013. In Selenga, runoff exhibits a significant decreasing trend (−1.3 km3/10yrs, p≤0.05), whereas a remarkable increasing trend (4.4 km3/10yrs, p≤0.05) occurs in Aldan. Given the negligible trends in precipitation over both basins, we attribute these contrasting changes to different impacts from warming-induced permafrost degradation. The Selenga basin, which is dominated by lateral degradation (i.e., decreasing permafrost extent), suffers from severe water loss via the enhanced infiltration of water that was previously stored close to the surface. This leads to a water-deficit surface condition. In the Aldan basin, in contrast, vertical degradation prevails: the thickened active layer is still underlain by a frozen layer with low permeability that sustains water-rich surface conditions. Furthermore, summer runoff shows contrasting oscillations, with wet-dry-wet-dry and dry-wet-dry-wet state evolutions in the Selenga and Aldan basins, respectively. We attribute such variabilities to the “seesaw-like” oscillations in summer precipitation associated with the propagation of Rossby wave trains across the Eurasian continent. We also find that warming-induced permafrost degradation over the 30-year period from 1984 to 2013 has led to strong regime shifts in river runoff in both basins. Our study highlights the importance of examining the mechanisms that drive changes in water availability from an integrated land-hydrology-atmosphere system perspective.
Gesehen am 23.02.2022